Beneficial Effects of Isoproterenol and Quinidine in the Treatment of Ventricular Fibrillation in Brugada Syndrome - Melissa Dakkak; Khyati Baxi; Ambar Patel (Case Reports in Cardiology)
The use of an implantable cardiac defibrillator has been advocated as the only effective treatment for the management of ventricular fibrillation (VF) in patients with Brugada Syndrome (BrS). However, this device is only useful for terminating VF. Intermittent and/or recalcitrant VF for which lifesaving cardioversion occurs is a problematic situation in this patient population. The immediate use of appropriate antiarrhythmics in the acute setting has proven to be lifesaving. Quinidine has been well established as an effective antiarrhythmic in BrS, while isoproterenol (ISP) has had some recognition as well. The addition of drug therapy to prevent the induction of these arrhythmias has been shown to reduce the morbidity and mortality associated with BrS. It was proven to be especially effective in the presence of early repolarization, evidenced by the reduction or normalization of the early repolarization pattern on ECG. Thus, for the prophylactic management and long term suppression of VF in BrS, further prospective studies should be performed to determine the effectiveness of quinidine and ISP in this patient population.